The Effect of Finishing and Polishing Time on Microleakage of Composite Restorations - Parvin Mirzakoucheki Boroujeni; Mehrdad Barekatain; Parisa Fattahi; Atefeh Fatemi; Laiya Zahraei; Ala Sharafi; Farid Fazeli (Islamic Dental Association of Iran, 2013)
Background and Aim : Composite resins require time to complete their polymerization. This process usually reaches its maximum rate after 24 hours. On the other hand, immediately after restoration, water sorption results in hygroscopic expansion of composite resins and the mentioned two factors usually reachequilibrium after a week. Considering the effect of mentioned processes on the microleakage of composite restorations, the purpose of the present study was to evaluate the effect of finishing and polishing time on the mean microleakage of composite restorations .   Materials and Methods : In this in-vitro experimental study, 60 sound human premolar teeth were selected. A standard Class V cavity was prepared measuring 1.5 mm in depth, 3 mm in width and 2 mm in length on the buccal surface of each tooth and incrementally restored with composite resin. Next, the teeth were randomly divided into 4 groups. The teeth in groups 1, 2, 3 and 4 were finished and polished immediately, 15 min, 24 h and one week after storage in distilled water at 37°C, respectively. Specimens in each group were subjected to 500 thermal cycles. The teeth were then coated with adhesive wax and nail varnish and immersed in 2% fuchsin solution for 24h. The specimens were washed and each sample was longitudinally sectioned in half by a diamond saw. Both halves were evaluated in terms of dye penetration under a stereomicroscope at 28X magnification. For each sample, the section with greater degree of microleakage was selected. Kruskal Wallis test and Mann Whitney U test were used for data analysis with a 99.1% confidence interval .   Results : The lowest mean microleakage was observed in the occlusal margin of group 3 teeth while the highest mean microleakage belonged to the occlusal and gingival margins of teeth in group 2. A significant difference was noted between the 4 groups in occlusal margin microleakage (P<0.009). However, no such difference was found in gingival margin .   Conclusion: This study showed that the finishing and polishing timewas effective on the mean microleakage in the enamel margin of composite restorations. The best time of finishing and polishing was 24h after the restoration. Time of finishing and polishing had no effect on microleakage in dentin margins of restorations .